Porous structures for the purification of biopharmaceuticals - Gonçalves, Bianca Leopoldo (2014)
This work aimed at the development of a (bio)polymeric monolithic support for biopharmaceuticals purification and/or capture. For that, it was assured that functional groups on its surface were ready to be involved in a plethora of chemical reactions for incorporation of the desired and most suitable ligand. Using cryogelation as preparation method a screening on multiple combinations of materials was performed in order to create a potentially efficient support with the minimal footprint, i.e. a monolithic support with reasonable mechanical properties, highly permeable, biocompatible, ready to use, with gravitational performance and minimal unspecific interactions towards the target molecules, but also biodegradable and produced from renewable materials. For the pre-selection all monoliths were characterized physico-chemically and morphologically; one agarose-based and two chitosan-based monoliths were then subjected to further characterizations before and after their modification with magnetic nanoparticles. These three specimens were finally tested towards adenovirus and the recovery reached 84% for the chitosan-GMA plain monolith prepared at -80°C. Monoliths based on chitosan and PVA were prepared in the presence and absence of magnetic particles, and tested for the isolation of GFP directly from crude cellular extracts. The affinity ligand A4C7 previously selected for GFP purification was synthesized on the monolith. The results indicated that the solid-phase synthesis of the ligand directly onto the monolith might require optimization and that the large pores of the monoliths are unsuitable for the purification of small proteins, such as GFP.